Pleomorphic Hyalinizing Angiectatic Tumor (PHAT): Review of the Literature with Case Presentation - Gerardo Cazzato; Anna Colagrande; Antonietta Cimmino; Teresa Lettini; Maria Teresa Savino; Carmen Martella; Giuseppe Ingravallo; Leonardo Resta (MDPI AG, 2021)
Pleomorphic hyalinizing angiectatic tumor (PHAT) is a very rare entity of soft tissue considered a "neoplasm of uncertain behaviour of connective or other soft tissue" by the World Health Organization (2020). It develops in subcutaneous tissue of the lower extremities, more frequently in the region of the ankle and foot, and rarely as a deep-seated soft tissue mass in locations such as the perineum, buttock, arms, head and neck, and viscera. Although inconsistent cytogenetic data have been reported on PHAT so far, there are potential morphological and genetic overlaps with hemosiderotic fibrolipomatous tumor (HFLT) and myxoinflammatory fibroblastic sarcoma (MIFS). Here we report a case of PHAT at the level of the upper third of the right thigh in a 48-year-old patient and we also focus on the differential diagnoses of these entities and conduct a literature review of reported cases.